REMOTE INTERNET VOTING FROM THE ANGLE OF PUBLIC TRUST: The cases of Switzerland, Canada, and Estonia - Syrivli, Zacharoula (My University, 2015)
The significance of trust to the adoption of electronic voting has been indicated by previous research. Recent evidence suggests that citizens’ trust is of great significance to remote Internet voting’s adoption. Factors found to be influencing the adoption of remote Internet voting are linked implicitly or explicitly to public trust. The research problem of this study is centered on the effect of trust on Internet voting’s adoption. In particular, this study aims at analysing the determinants that make some voters repose trust in Internet voting. The main theoretical focus is to deepen the understanding of the concept of trust and its role in Internet voting’s adoption. This study adopts a case study approach where the contexts of Switzerland, Canada and Estonia are evaluated comparatively. This study is also based on official reports and published survey results. Public trust is largely dependent on contextual factors, such as the enactment of specific legislation, high level of Internet penetration, inauguration of a publicity campaign aiming at informing citizens regarding remote Internet voting as well as trials and technological tests prior to online voting’s implementation. Public trust is also influenced by behavioural factors, such as confidence in new technologies, computing literacy, high frequency of Internet use and individual’s perception regarding his IT skills. The significance of the impact of voter’s perception regarding remote Internet voting’s security on the development of trust emerges also from the findings of this study. It can be concluded that the successful implementation of remote Internet voting does not lie in its perfect system but in electorate’s trust to the contrary. In particular, a high level of trust in the internet voting procedure signifies actual and constant use of online voting.
Keywords: remote Internet voting; technology trust; case study; fi=Julkisjohtaminen|en=Public Management |